Diagnostic fine-needle aspiration cytology and immunocytochemistry analysis of a primary thyroid lymphoma presenting as an anatomic emergency. - Van den Bruel, A; Drijkoningen, M; Oyen, R; Vanfleteren, E; Bouillon, R (2002)
The case of a 66-year-old woman with rapidly progressive respiratory distress caused by a massive anterior neck mass with tracheal compression is presented. Within 24 hours, fine-needle aspiration cytology (FNAC) and immunocytochemistry provided a diagnosis of high-grade B-cell lymphoma and the opportunity to institute a chemotherapeutic regimen resulting in a rapid volume reduction and airway expansion. One year after combined modality treatment the patient was in complete remission (with an estimated thyroid volume of 4 cm3). This case report illustrates the advantages of FNAC and immunocytochemistry in the diagnosis of thyroid lymphoma.